2017
DOI: 10.1186/s13568-017-0376-3
|View full text |Cite
|
Sign up to set email alerts
|

Importance of stress-response genes to the survival of airborne Escherichia coli under different levels of relative humidity

Abstract: Other than the needs for infection control to investigate the survival and inactivation of airborne bacterial pathogens, there has been a growing interest in exploring bacterial communities in the air and the effect of environmental variables on them. However, the innate biological mechanism influencing the bacterial viability is still unclear. In this study, a mutant-based approach, using Escherichia coli as a model, was used to prove the concept that common stress-response genes are important for airborne su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Thus, the continuous expression of Catalase in our study implies that C. cladosporioides is always encountering an oxidative stress under dry periods. This meets the expectation that oxidative stress is an important stress under limited water availability conditions—particularly at 60% RH, because oxidative stress is relatively mild at higher RH (80%), and other types of stress are more detrimental than oxidative stress when the RH is further reduced below 60% …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, the continuous expression of Catalase in our study implies that C. cladosporioides is always encountering an oxidative stress under dry periods. This meets the expectation that oxidative stress is an important stress under limited water availability conditions—particularly at 60% RH, because oxidative stress is relatively mild at higher RH (80%), and other types of stress are more detrimental than oxidative stress when the RH is further reduced below 60% …”
Section: Discussionmentioning
confidence: 89%
“…This meets the expectation that oxidative stress is an important stress under limited water availability conditions-particularly at 60% RH, because oxidative stress is relatively mild at higher RH (80%), and other types of stress are more detrimental than oxidative stress when the RH is further reduced below 60%. 27,28…”
Section: The Crucial Role Of Oxidative Stress In Mold Growth Under mentioning
confidence: 99%
“…To determine the bacterial survival, both culturable and DNA counts of the collected bacteria were measured. The plate-count method and the DNA counts by quantitative polymerase chain reaction (qPCR) were used for determination of the culturability of the bacterial cells [30]. In brief, bacterial DNA was extracted using a QIAamp DNA Mini Kit (Qiagen, Hilden, Germany) following the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Another study showed that the viability of Pseudomonas fluorescens bacteria decreased by over 50% after 90 min of continuous aerosolization [118]. The sublethal damages occurring during aerosolization were associated to a differential gene expression of respiratory, cold-shock, metabolism, and more generally stress-response genes [117][118][119][120][121]. Aerosolization in small and salty liquid droplets that dry rapidly was shown to induce a higher survival rate of Pseudomonas syringae [115].…”
Section: Effects Of Atmospheric Conditions On Microbial Life During Amentioning
confidence: 99%